2003
DOI: 10.1016/s0195-668x(03)00480-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone on circulating cytokine network, and left ventricular contractile performance and geometry in patients with idiopathic dilated cardiomyopathy

Abstract: GH administration modulates beneficially circulating cytokine network and soluble adhesion molecules in patients with DCM, whilst enhancing contractile reserve and diminishing LV volumes. These GH-induced anti-inflammatory effects may be associated with the improvement in LV contractile performance and exercise capacity as well as with the reverse of LV remodelling of patients with DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
44
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 42 publications
4
44
0
1
Order By: Relevance
“…Analysis of the heart by echocardiography and equilibrium radionuclide angiography confirmed treatment-related improvements in structure and function [6, 21]. These observations strongly indicate a direct or indirect effect of GH on cardiac contractility, which may have contributed to improvements in exercise capacity and performance observed in patients receiving GH replacement therapy [24, 30]. …”
Section: Cardiac Contractilitymentioning
confidence: 88%
See 3 more Smart Citations
“…Analysis of the heart by echocardiography and equilibrium radionuclide angiography confirmed treatment-related improvements in structure and function [6, 21]. These observations strongly indicate a direct or indirect effect of GH on cardiac contractility, which may have contributed to improvements in exercise capacity and performance observed in patients receiving GH replacement therapy [24, 30]. …”
Section: Cardiac Contractilitymentioning
confidence: 88%
“…Pre-clinical and clinical studies have indicated that GHD can have an adverse effect on the contractility of cardiac muscle [29, 30]. A study by Longobardi et al (1998) also reported that patients with both adult- and childhood-onset GHD present a reduced cardiac ejection fraction compared with control subjects [4]; in particular, exercise was found to reduce ejection fraction in GH-deficient patients, whereas it was increased in healthy subjects [4].…”
Section: Cardiac Contractilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Adamopoulos S. и соавт. [1] предложили еще один механизм, за счет которого ГР может быть полезным при лечении ХСН. В рандомизированном перекрестном исследовании с участием 12 пациентов с ДКМП 3-месячный курс применения ГР вызывал уменьшение уровня провоспалительных цитокинов в крови, а также таких маркеров повреждения, как фак-тор некроза опухолей (TNF-a), интерлейкин-6 (IL-6), гранулоцит-макрофаг-колониестимулирующий фак-тор и его растворимый рецептор, макрофаг-хемопри-влекающий протеин.…”
Section: '2010unclassified